The essential AI skills and knowledge that business accounting students should acquire - Moran, Wilfredo (Journal of Management and Business Education, 2025)
This paper examines the transformative impact of artificial intelligence (AI) on the accounting profession, the need for curriculum reform in accounting education, and the essential AI skills and knowledge that business accounting students should acquire. It explores the essential AI skills and knowledge required for future accountants to thrive in an AI-driven landscape. These include technical proficiencies in data management, programming fundamentals, AI and machine learning concepts, and AI-specific accounting software. Analytical and interpretive skills encompassing data analysis, statistical modeling, predictive analytics, and critical evaluation of AI outputs are equally crucial. Furthermore, the paper emphasizes the importance of professional and soft skills such as communication, critical thinking, professional skepticism, business acumen, adaptability, and ethical awareness. By integrating these competencies into accounting curricula, educational institutions can effectively prepare future accountants for the challenges and opportunities presented by AI, ensuring they possess the skills and knowledge to navigate the evolving landscape of the profession. The aim is to provide a roadmap for equipping future accountants with the competencies needed to thrive in the evolving world of AI-driven finance and business.